Genome-wide significant association with seven novel multiple sclerosis risk loci. Issue 12 (16th October 2015) - Lill, Christina M; Luessi, Felix; Alcina, Antonio; Sokolova, Ekaterina A; Ugidos, Nerea; de la Hera, Belén; Guillot-Noël, Léna; Malhotra, Sunny; Reinthaler, Eva; Schjeide, Brit-Maren M; Mescheriakova, Julia Y; Mashychev, Andriy; et al.
Abstract : Objective: A recent large-scale study in multiple sclerosis (MS) using the ImmunoChip platform reported on 11 loci that showed suggestive genetic association with MS. Additional data in sufficiently sized and independent data sets are needed to assess whether these loci represent genuine MS risk factors. Methods: The lead SNPs of all 11 loci were genotyped in 10 796 MS cases and 10 793 controls from Germany, Spain, France, the Netherlands, Austria and Russia, that were independent from the previously reported cohorts. Association analyses were performed using logistic regression based on an additive model. Summary effect size estimates were calculated using fixed-effect meta-analysis. Results: Seven of the 11 tested SNPs showed significant association with MS susceptibility in the 21 589 individuals analysed here. Meta-analysis across our and previously published MS case-control data (total sample size n=101 683) revealed novel genome-wide significant association with MS susceptibility (p<5×10 −8 ) for all seven variants. This included SNPs in or near LOC100506457 (rs1534422, p=4.03×10 −12 ), CD28 (rs6435203, p=1.35×10 −9 ), LPP (rs4686953, p=3.35×10 −8 ), ETS1 (rs3809006, p=7.74×10 −9 ), DLEU1 (rs806349, p=8.14×10 −12 ), LPIN3 (rs6072343, p=7.16×10 −12 ) and IFNGR2 (rs9808753, p=4.40×10 −10 ). Cis expression quantitative locus effects were observed in silico for rs6435203 on CD28 and for rs9808753 on several immunologically relevant genes in the IFNGR2 locus. Conclusions: This study adds seven loci to the list of genuine MS genetic risk factors and further extends the list of established loci shared across autoimmune diseases.